Production and quality of silages pearl millet and paiaguas palisadegrass in monocropping and intercropping in different forage systems (Bioscience Journal, 2018)
: With the arrival of new early genotypes and high nutritive value and productive potential, millet has been gaining prominence in recent years for the production of silage, and it promises lower costs of production. Thus, the consortium of millet with tropical forages can increase the production of silage, providing more food to be used in the offseason, where there is low availability of forage. The objective of this study was to evaluate the dry mass production, fermentative characteristics and chemical-bromatological of pearl millet silage and Paiaguas palisadegrass in monocropping and intercropping in different forage systems in the second cropping season. The experimental design consisted of randomized blocks with four replicates. The treatments consisted of silage of the following forage systems: monocropped pearl millet, monocropped Paiaguas palisadegrass, pearl millet intercropped in rows with Paiaguas palisadegrass, pearl millet intercropped inter-row with Paiaguas palisadegrass, and pearl millet oversown and intercropped with Paiaguas palisadegrass (totaling 20 experimental plots). The consortium of pearl millet with Paiaguas palisadegrass contributed to raise the dry matter contents of the silages, except in the system using the overgrowth. Pearl millet silages monocropped and intercropped with Paiaguas palisadegrass presented reductions in pH and ammoniacal nitrogen values as well as favor lactic fermentation. Pearl millet monocropped and intercropped silage exhibited better fermentative and bromatological characteristics than silage obtained from monocropped Paiaguas palisadegrass. Therefore, creating silage from intercropped forages provides an interesting supplemental roughage option that can be used during the offseason for animal feeding.